1999
DOI: 10.1021/jo982280v
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Anodic Olefin Coupling Reactions:  The Use of Allylsilane Coupling Partners with Allylic Alkoxy Groups

Abstract: Intramolecular anodic olefin coupling reactions having an alkoxy substituent on the allylic carbon of an allylsilane moiety have been studied. These substrates were examined as part of an effort to determine the compatibility of the anodic olefin coupling reaction with the presence of very acid-sensitive functional groups and the construction of functionalized five-membered rings. In the initial experiment reported, an enol ether moiety was coupled to a trisubstituted allylsilane to afford a five-membered ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Some of the most substantial advancements in electrochemical oxidative coupling reactions of the past 20 years have been developed by the Moeller and Wright groups. In this way, anodic oxidation has been shown to enable the coupling of two nucleophilic functional groups, thereby leading to new broadly useful umpolung disconnections.…”
Section: Electrochemistry Vignettes In Synthesismentioning
confidence: 99%
“…Some of the most substantial advancements in electrochemical oxidative coupling reactions of the past 20 years have been developed by the Moeller and Wright groups. In this way, anodic oxidation has been shown to enable the coupling of two nucleophilic functional groups, thereby leading to new broadly useful umpolung disconnections.…”
Section: Electrochemistry Vignettes In Synthesismentioning
confidence: 99%
“…Moeller also demonstrated that an ordered double layer can improve selectivity in an intramolecular cyclisation reaction by promoting cyclisation over solvent trapping (Figure 15 C). [193][194][195] Thea nodic oxidation and the ensuing cyclisation occur within the ordered environment of the double layer at the anode surface,w hich slows diffusion and excludes the methanol from the electrode surface that could otherwise interfere with cyclisation. Silyl protection of the internal alcohol moiety of the substrate was still necessary to prevent the intramolecular trapping by this competing nucleophile.…”
Section: Methodsmentioning
confidence: 99%
“…Here, atom-economical and regioselective platforms for direct functionalization of double or triple bonds allow access to a range of functionalized products, thereby offering considerable opportunities for strategic chemical synthesis. In addition to the intramolecular anodic olefin coupling reactions discussed in the previous section, other carbon- [849][850][851][852][853][854][855][856][857][858][859][860][861][862] as well as oxygen-based [863][864][865][866][867][868][869][870][871][872][873][874][875] nucleophiles have also been utilized in radical cation-initiated cyclization protocols for constructing C-C and C-O bonds, respectively. Furthermore, Moeller and coworkers have designed systems for direct functionalization of alkenes using nitrogen functionalities as trapping groups.…”
Section: Amination Of Alkenes and Alkynesmentioning
confidence: 99%